Effect of ethephon levels and amino acids on the growth characteristics of oat crop - Hassan, Haider H.; Zaibel, Doaa N.; Zaidan, Safaa A.; Shadhan, Jameel S. (Acta Agraria Debreceniensis, 2023)
A field experiment was conducted during the 2021-2022 season in an agricultural field in Basra Governorate. The aim was to study the effect of spraying ethephon and amino acids on the growth characteristics of oats (Avena sativa L.) Shifa cultivar. The experiment involved three levels of ethephon (0, 0.240, and 0.600 kg ha-1), represented by the symbols E0, E1, and E2 respectively, and two spray levels of amino acids (0 and 5 ml L-1), represented by the symbols A0 and A1. A factorial experiment was applied using the R.C.B.D (randomized complete block design) in a split plots arrangement with three replications. The results revealed significant differences in the levels of ethephon for most of the studied characteristics. The level of 0.240 kg ha-1 (E1) was superior in terms of chlorophyll content, crop growth rate, and the number of tillers, with increases of 39.07%, 39.26%, and 16.36%, respectively, compared to the control treatment (E0). Regarding the amino acids treatments, spraying at a concentration of 5 ml L-1 (A1) demonstrated significant superiority, resulting in the highest plant height, flag leaf area, chlorophyll content, and crop growth rate. This study concludes that amino acids play a crucial role in plant growth, and the combination of 5 ml L-1 amino acids with 0.240 kg ha-1 of ethephon significantly increased chlorophyll content and crop growth rate.